The results of experimental studies to assess the efficiency of hot water treatment of asphalt-resin-paraffin deposits - V. S. Gorbachenko (Наука. Инновации. Технологии, 2025)
One of the key problems of oil production at the Pripyat Trough fields is the formation of asphalt-resin-paraffin deposits (ARPD) on underground equipment. These deposits significantly complicate the operation of wells and can lead to a decrease in their productivity. There is a large number of methods for combating ARPD, which differ in the principles of action on deposits. The most common method to tackle ARPD in the Belarusian region is the technological treatment with hot water. This method helps to remove ARPD, restoring the normal operation of the equipment. The study presents the methodology for conducting experimental studies aimed at assessment of the effectiveness of thermal action on ARPD under various hot water injection modes during the technological treatment. As part of the research, tests were conducted using various coolant injection parameters to determine the optimal conditions for maximum efficiency. The paper also presents a method to enhance the efficiency of thermal treatment with hot water. The main principle is to increase the flow rate of hot liquid injected into the well. This allows reducing heat losses into the rock in the wellhead interval, which in turn improves the heating of the liquid in the column of pump-compression pipes at depths of more than 100 meters. The results of field studies have shown that an increase in the flow rate of injected hot water significantly intensifies the efficiency of heat treatment compared to the standard approach. This confirms the feasibility of using the proposed method for removing ASPD from the working surface of deep-well pumping equipment.